Methodological problems of neopatrimonialism research - Kareli, Teimuraz ("Intercultural Dialogues" Transactions, 2023)
The paper is devoted to the methodological problems of neopatrimonialism research. The relevance of the problem research is explained in the introductory part. The concept of neo-patrimonialism has much more predictive power than other concepts in saying that political transitions do not show a gradual consolidation of democratic institutions. On the contrary, hybrid regimes are created in neo-patrimonial states, in which democratic Western-type institutions (separation of power, electoral rights, constitution) are only the shield that overshadows real political processes. Their internal logic is subject to the established traditional type of political domination. The validity of this theory is confirmed by the so-called political processes. In the "post-Soviet" space, where, over time, the construction of such (only outwardly democratic) hybrid regimes becomes obvious. According to the author, using neo-institutional theory, it is possible to explain the functionality of neo-patrimonial regimes with both structural and dynamic aspects. The research problems are listed in the paper: in particular, there is still no unified opinion in the understanding of some basic issues: what does the prefix "neo" mean in the term neopatrimonialism; What is the relationship between legal-rational and traditional dominance in neopatrimonialism regimes; What is common between this term and the concept of patrimonialism; How can neopatrimonialism be operationalized; How to distinguish it from such phenomena as clientelism, nepotism, clanism. The power and defining character of informal relations in the Georgian political-administrative system ("telephone law", Blatt, nepotism, client-patronage network, etc.) is researched. In the concluding part, it is mentioned that the concept of neo-patrimonialism has great potential in neo-institutional theory. Neopatrimonialism refers to the fusion of the traditional core and the legal shell. Thus, it is necessary to research non-obvious forms of institutionalization of traditional institutions, informal practices. For these purposes, neo-institutionalism offers the most appropriate understanding of institutions and institutional change. From our point of view, the further development of the concept of neopatrimonialism should be closely related to the achievements and methodological apparatus of new institutionalism.